Development of a research project repository - Somefun T. E.; Awosope C. O. A.; Sika C. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The advances of technology resulting in the proliferation of mobile devices have changed the way we live and have necessitated the restructuring of the educational system. This can be employed to aid student’s participation in research studies. This study aims at promoting- research in universities amongst students by giving them the opportunity to exercise their scholarly abilities, easy access to research projects carried out by other students, collaboration with other students with similar research inclinations as well as gain visibility before the school management or companies interested in granting scholarships to outstanding works. This project is implemented using JavaScript, HTML and CSS for the front-end; Node.js, a JavaScript framework for the back-end and MongoDB for the database. It is a web application that enables the students to upload their research works, view the research of others and collaborate with peers. This system has a high potential to enhance student participation in universities’ research studies.